Disparidades sociais e experiências discriminatórias vivenciadas por estudantes de Odontologia: o papel da interseccionalidade - Jhonathan Lopes-Silva (2022)
The aim of this study was to evaluate the social characteristics and form of admission of dental students in the university, associating these characteristics with the discriminatory experiences lived by then, through an intersectional analysis. A cross-sectional multicenter study was conducted with Brazilian dental students, selected through a snowball sample. The study was approved by the Ethics Committee for Human Research of the Federal University of Minas Gerais (CAAE: 47622121.4.0000.5149). The discriminatory experiences were measured by the total score of Explicit Discrimination Scale (EDS). To evaluate the other variables, a questionnaire was created with thematic blocks: sociodemographic and socioeconomic characteristics and admission at dental school. After the development of the questionnaire, meetings with experts on the subject and on the scientific methods were conducted to adjust it. Next, cognitive interviews with six volunteer students were conducted to verify the applicability and understanding of the instrument. After the adjusts, a pilot study was conducted, and no changes were needed. Students were invited to answer the full questionnaire and the EDS via Google Forms. Data was analyzed by descriptive analysis, bivariate analysis using Mann-Whitney and Kruskal-Wallis with post-hoc test. Multiple analysis using Poisson regression with robust variance was performed to measure the intersectionality. The significance level was set at 5% (p<0.05). 531 students from 15 different Brazilian institutions participated of this study; 74.2% were female, 53.3% white, 99.6% cisgenders and 85.5% heterosexuals. The mean age was 25.4 (±6.3) years. The means of discriminatory experiences were higher in students who work and support themselves (7.27±6.6) or use public policies (7.03±5.79) to access the university. Four models were built for an intersectional analysis. In the first model with non-adjusted analysis, black students were more likely to have had discriminatory experiences (PR:1,503 95% CI: 1.305-1.731). In the second model, the variable sex was incorporated, and the association between race and discriminatory experiences were kept (PR:1.513; 95% CI: 1.314-1.742). The monthly income was incorporated in the third model. Black race (PR=1.502; 95% CI: 1.304-1.729) and lower monthly income (PR=1.234; 95% CI: 1.057-1.442) were statistically associated with discriminatory experience. The last adjusted model was composed by race, sex, monthly income and sexual orientation and it was observed that black students (PR=1.484; 95% CI: 1.291-1.705; p<0.001), women (PR=1.227; 95% CI: 1.030 -1.462; p=0.022), with lower monthly income (PR=1.212; 95% CI: 1.043-1.409; p=0.012) and LGBTQIAP+ (PR=1.466; 95% CI: 1.238-1.735; p<0.001) had higher probability of having discriminatory experiences when compared to whites, men, with higher monthly income and heterosexuals. It can be concluded that the profile of dental students maintained a certain pattern: white, heterosexual and cisgender. Students who use public policies of access have higher averages of discrimination. Also, black female students with lower monthly income and LGBTQIAP+ were more likely to have had discriminatory experiences when compared to white men with highly monthly income and heterosexual.